2007
DOI: 10.1104/pp.107.096206
|View full text |Cite
|
Sign up to set email alerts
|

ELF4Is Required for Oscillatory Properties of the Circadian Clock

Abstract: Circadian clocks are required to coordinate metabolism and physiology with daily changes in the environment. Such clocks have several distinctive features, including a free-running rhythm of approximately 24 h and the ability to entrain to both light or temperature cycles (zeitgebers). We have previously characterized the EARLY FLOWERING4 (ELF4) locus of Arabidopsis (Arabidopsis thaliana) as being important for robust rhythms. Here, it is shown that ELF4 is necessary for at least two core clock functions: entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
133
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(154 citation statements)
references
References 55 publications
21
133
0
Order By: Relevance
“…The elf3 mutants show a comparable first peak in DD (12,14). The question is whether this single CAB2::LUC peak in elf3 represents bona fide oscillator activity or, instead, reflects the last driven cycle of a clock that is running down after receiving a final zeitgeber before free run (32). We favor the latter interpretation and for this reason our characterization of elf3-1 focused mainly on the behavior of TOC1::LUC + expression, because this reporter in WT was strongly rhythmic in the dark following light or temperature entrainment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The elf3 mutants show a comparable first peak in DD (12,14). The question is whether this single CAB2::LUC peak in elf3 represents bona fide oscillator activity or, instead, reflects the last driven cycle of a clock that is running down after receiving a final zeitgeber before free run (32). We favor the latter interpretation and for this reason our characterization of elf3-1 focused mainly on the behavior of TOC1::LUC + expression, because this reporter in WT was strongly rhythmic in the dark following light or temperature entrainment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Research efforts in this direction have placed EARLY FLOWERING 4 (ELF4) within the oscillator as a key circadian repressor. 17,18,24,25 Other studies have shown that post-translational modifications, including protein targeted degradation and protein phosphorylation are essential for the function of the plant circadian clock. As an example, it has been shown that ZEITLUPE (ZTL), a light-sensitive protein, binds to TOC1 during the night, directing TOC1 to degradation by the proteasome.…”
Section: The Arabidopsis Thaliana Circadian Clockmentioning
confidence: 99%
“…These include genes such as ELF3, 43 ELF4, 25 TIME FOR COFFEE, 44,45 SENSITIVITY TO RED LIGHT REDUCED (SRR1), 46 LIGHT INSENSITIVE PERIOD 1 (LIP1), 47,48 and XAP5 CIRCADIAN TIMEKEEPER (XCT ). 49 None of these genes encode a protein with apparent chromophore interactions, required as a canonical domain involved in light perception, which suggests that their protein products act as signaling components in a step downstream of the light signal perception.…”
Section: Aba and Non-aba Stress Responses: Drought Cold And Osmotic mentioning
confidence: 99%
“…CCA1 and LHY bind directly to the promoter of TOC1, negatively regulating TOC1 expression, and TOC1 participates in the positive regulation of CCA1 and LHY expression through an unknown mechanism (Alabadí et al, 2001). Other genes, such as LUX ARRHYTHMO, also known as PHYTOCLOCK1, GI-GANTEA (GI), EARLY FLOWERING3 (ELF3), ELF4, TIME FOR COFFEE, and PSEUDORESPONSE REGU-LATOR3/5/7/9 (PRR3/5/7/9), have also been suggested to function in or close to the central oscillator (Doyle et al, 2002;Hazen et al, 2005;Locke et al, 2005;Nakamichi et al, 2005;Edwards et al, 2006;Gould et al, 2006;Ding et al, 2007;McWatters et al, 2007).…”
mentioning
confidence: 99%